Last visit was: 17 Jun 2024, 00:27 It is currently 17 Jun 2024, 00:27
Toolkit
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

# If f(x) = x^4 - 3x^3- 2x^2 + 5x , then f(-1) =

SORT BY:
Tags:
Show Tags
Hide Tags
Math Expert
Joined: 02 Sep 2009
Posts: 93696
Own Kudos [?]: 632376 [3]
Given Kudos: 82322
Senior Manager
Joined: 28 Feb 2014
Posts: 269
Own Kudos [?]: 322 [0]
Given Kudos: 132
Location: United States
Concentration: Strategy, General Management
Manager
Joined: 13 Dec 2013
Posts: 50
Own Kudos [?]: 82 [1]
Given Kudos: 35
Location: Iran (Islamic Republic of)
Math Expert
Joined: 02 Sep 2009
Posts: 93696
Own Kudos [?]: 632376 [0]
Given Kudos: 82322
Re: If f(x) = x^4 - 3x^3- 2x^2 + 5x , then f(-1) = [#permalink]
Bunuel wrote:
If f(x) = x^4 - 3x^3- 2x^2 + 5x , then f(-1) =

A. -5
B. -3
C. -1
D. 1
E. 3

Kudos for a correct solution.

MAGOOSH OFFICIAL SOLUTION:
Attachment:

evaluatingfx_text.PNG [ 9.29 KiB | Viewed 7386 times ]
Senior Manager
Joined: 24 Nov 2015
Posts: 406
Own Kudos [?]: 125 [0]
Given Kudos: 231
Location: United States (LA)
Re: If f(x) = x^4 - 3x^3- 2x^2 + 5x , then f(-1) = [#permalink]
$$f(x)=x^4-3x^3-2x^2+5x$$
we have to find value for f(-1)
$$(-1)^4-3(-1)^3-2(-1)^2+5(-1)$$
it works out to be equal to -3
Tutor
Joined: 05 Apr 2011
Status:Tutor - BrushMyQuant
Posts: 1787
Own Kudos [?]: 2121 [0]
Given Kudos: 100
Location: India
Concentration: Finance, Marketing
Schools: XLRI (A)
GMAT 1: 700 Q51 V31
GPA: 3
WE:Information Technology (Computer Software)
Re: If f(x) = x^4 - 3x^3- 2x^2 + 5x , then f(-1) = [#permalink]
Top Contributor
Given that f(x) = $$x^4 - 3x^3- 2x^2 + 5x$$ and we need to find the value of f(-1)

To find f(-1) we need to compare what is inside the bracket in f(-1) and f(x)

=> We need to substitute x with -1 in f(x) = $$x^4 - 3x^3- 2x^2 + 5x$$ to get the value of f(-1)

=> f(-1) = $$(-1)^4 - 3(-1)^3- 2(-1)^2 + 5*-1$$ = 1 -3*-1 - 2*1 - 5 = 1 + 3 - 2 - 5 = -3